Estrategias indagatorias para el mejoramiento de las competencias del área de ciencia y tecnología en los estudiantes de cuarto grado de secundaria de La Institución Educativa Parroquial Virgen de Loreto, Iquitos 2024 - López Lomas, Pedro Segundo (2025)
The purpose of the study was to determine whether inquiry strategies contribute to the improvement of competencies in the area of science and technology of students in the 4th year of secondary school at I.E. Virgen de Loreto, Iquitos year 2024. We chose the type of evaluative research with a quasi-experimental design, in which we opted for the application of pre-test and post-test in the experimental and control groups; the population considered 70 students distributed in two groups of 35 students each, 4°A and 4°B. A 20-question Likert scale questionnaire was used to assess competencies before and after the intervention. The findings showed significant differences in favor of the experimental group, with an increase of 6.86 points in general science and technology competencies (p=0,002), inquiry competency increased by 4,02 points (p <0,01), explanation of the physical world competency improved by 2,13 points (p=0,003) and elaboration of technological solutions competency increased by 2,17 points (p=0,001), 17 points (p=0,001), which means that inquiry strategies are highly effective in strengthening science and technology competencies through the use of meaningful, active and experiential learning, which supports their continued implementation as a technique for strengthening the academic performance of schoolchildren.